Leadership in knowledge management / Raja Abdullah Yaacob and Mazwani Ayu Mazlan - Yaacob, Raja Abdullah; Mazlan, Mazwani Ayu (Faculty of Information Management, 2010)
Knowledge is regarded as one of the most highly valued commodities in modern economic activity, hence the emergence of a knowledge-based economy. It is identified as one of the most crucial resources that adds value to the competitive advantage. In a knowledge-based organization, knowledge becomes a key factor for business success and our brain constitutes as part of the means of production. In accelerating the knowledge sharing and creation, most organizations have invested heavily in information and communication ICT and training. They attempt to share and reuse new knowledge and often find it very difficult to disseminate within the organization. In this context, leaders must play the key role in getting organizations cope with the challenges faced from the expanding growth of knowledge.